A case of foetal macrosomia - Acharya, Pushpashree; Singh, Sanjay (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Fetal macrosomia is an upcoming challenge in the field of obstetrics due to its rising incidence. The incidence varies according to ethnicity, genetic differences and anthropometric discrepancies between populations. Obesity, previous history of macrosomia, multiparity, diabetes and post-dated pregnancy are few risk factors associated with macrosomia. Management of macrosomia is a big challenge as no precise guidelines have been set. Macrosomia is associated with multiple maternal and foetal complications like operative delivery, post partum haemorrhage, perineal trauma, shoulder dystocia, brachial plexus injury, skeletal injury, birth asphyxia etc. We report a case of foetal macrosomia, weighing 5.5kg which was delivered by LSCS to a woman having BMI - 26.6kg/m² with 39 weeks of pregnancy with history of previous LSCS. There was no maternal or foetal complication. There was no history of diabetes in present pregnancy and inter conception period. Because of rarity of this condition we report this case of foetal macrosomia with a short review of literature.